IMPROVING STUDENTS’ SPEAKING ABILITYBY BOARD GAME FOR THE SECOND GRADE STUDENTS OF MTS NW DARUSSOLIHIN KALIJAGAIN ACADEMIC YEAR 2019/2020 - MASHUR MASHUR (LPPM Universitas Gunung Rinjani, 2020)
In teaching and learning speaking process, there are some problems of the teachers such as: the mastery of approach and methods. English teachers have to try to find out and apply proper some strategies in the teaching learning speaking process. As the motivator for students,the teacher should be look carefully and able to overcome and lookcoused of the problem for the problem solving of their students’ problems. They have to apply appropriate method and approach based on the situation and condition of the students and their environment. In this case, board game is one of approaches which is expected to be able to increase students’ speaking ability. In this research, the writer formulated two problems: (1) To what extent is the student's speaking ability for the eighth grade of MTs NW Darussolihin Kalijagain the school year 2019-2020? and (2) What is the effect of board game in improving the students’ speaking ability at the second grade of MTs NW Darussolihin Kalijagain the school year 2019/2020. ? This research was an experimental study. The sample of the study was divided into two groups; experimental group and control group, then the two groups were given the same test. Furthermore, this research used speaking test as the instrument to collect the data. Moreover, the researcher used hypothesis testing to measure the students speaking ability. After that,analyzed the data which were obtained from the experimental group in which they were taught by applying scaffolding talk and the control group was taught by using traditional method.The result of the data analysis indicated that the eighth grade students of MTs NW Darussolihn Kalijaga attained high score on the post test for experimental group. It was the fact that the effectiveness of board game talk was indicated by the mean score of the students that was 58.65. Furthermore, it was also indicated by the result of hypothesis testing that the alternative hypothesis was accepted. It was provable that the t-table was lower than t-test in which the t-table was 1.68 and t-test 7.16. Therefore, it can be concluded that the experimental group had higher ability in speaking skill than the control group.